Sacred Objects as Cultural Assets of the Roztocze National Park and Its Buffer Zone - Paweł Pytka (Barometr Regionalny, 2015)
Cultural landscape is an important element in determining the attractiveness of a given tourist area. Its specific elements are places of worship. Integrated into a unique natural landscape they can become a kind of gem, and their many values can be a significant stimulant to tourism. This article presents the religious buildings and objects located within the Roztocze National Park and its buffer zone: churches, various types of shrines, roadside crosses and statues and cemeteries. These places, besides performing their sacral function, are important for local communities: they are places of meetings, exchanges of views and solving problems. What is also important is the cultural aspect of these sites, together with their historical value. These various qualities of sacred objects can generate an increase in tourism throughout the entire region.